ANDERSON, J. ; DUNCAN, S. ; HUDSON, R. Redundant spaces in cities and regions? Studies in industrial decline and social change - Clos, Isabel (Documents d’Anàlisi Geogràfica, 1985)
ANDERSON, J. - DUNCAN, S. - HUDSON, R. (eds,), Redundant Spaces in Cities aud Regions? Studies in Industrial Decline and Social Change; Institute of British Geographers Special Publication no 15; 354 pp. Londres 1983.